PRODUCTION COSTS IN MAINTAINING THE EXISTENCE OF BUSINESS QUALITY AT KIFA BAKERY AND CAKE - Saputri, Alisia Pingky; Aprillia, Hendra Safira; Fitriana, Noor Laila (Sharia Business Management UIN Raden Intan Lampung, 2024)
The cost of production is important to determining the selling price of products which can provide profits for the company, so that it is able to compete with other competitors. Good product quality can support the sustainability of a business. Therefore, there are quality costs for companies to produce the best quality to provide satisfaction to consumers who buy. The aim of this research is to explain the production costs used by Kifa Bakery and Cake in maintaining business existence in an era of increasing competition in the bakery business. This research uses descriptive qualitative methods with primary data sources in the form of interviews with Kifa Bakery and Cake business owners. Apart from that, the use of secondary data originating from literature reviews to strengthen the results of research analysis. The results of the research state that the cost of production used by Kifa Bakery and Cake is quite high in maintaining product quality and business existence, so that Kifa Bakery and Cake always provides a sense of satisfaction to customers and a business existence that is widely known to the public.